Evidence-based risk stratification for sport medicine procedures during the COVID-19 pandemic - Hinckel, B. B.; Baumann, C. A.; Ejnisman, L.; Cavinatto, L. M.; Martusiewicz, A.; Tanaka, M. J.; Tompkins, M.; Sherman, S. L.; Chahla, J. A.; Frank, R.; Yamamoto, G. L.; Bicos, J.; et al. (Journal of the American Association of Orthopaedic Surgeons: Global Research & Reviews, 2020)
Orthopaedic practices have been markedly affected by the emergence of the COVID-19 pandemic. Despite the ban on elective procedures, it is impossible to define the medical urgency of a case solely on whether a case is on an elective surgery schedule. Orthopaedic surgical procedures should consider COVID-19-associated risks and an assimilation of all available disease dependent, disease independent, and logistical information that is tailored to each patient, institution, and region. Using an evidence-based risk stratification of clinical urgency, we provide a framework for prioritization of orthopaedic sport medicine procedures that encompasses such factors. This can be used to facilitate the risk-benefit assessment of the timing and setting of a procedure during the COVID-19 pandemic.